ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OUTCOME EKSTUBASI DI ICU RSUD Prof. Dr. MARGONO SOEKARDJO PURWOKERTO - Barkah Waladani; Henny Suzana Mediani; Anastasia Anna (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Management airways become one important part in an act of care in patients with critical conditions due to disease. One attempt to keep the airway is to intubate, is inserting a pipe into the upper respiratory tract. The main requirement that must be considered is to keep the airway is always free and breath can run smoothly and orderly. The final stage of intubation was extubated. The purpose of this study was to determine what factors are associated with outcome of extubation in ICU Prof. Dr. Margono Soekardjo Purwokerto Hospital. This study is a cohort retrospective with  analytic correlational design.The sample in this study amounted to 96 people. Bivariate test results that there is a relationship between age (p = 0.000), tidal volume (p = 0.001), systolic blood pressure (p = 0.000), FiO2 (p = 0.007) and PEEP (p = 0.014) with outcome of extubation. There is no associated GCS (p = 0.358) with outcome of extubation. Therefore, nurses need to give special attention regarding the condition of the patient, such as age characteristics, the value of tidal volume, systolic blood pressure, FiO2 and PEEP before extubation. Keywords: outcome, extubation, ICU